2020
DOI: 10.1177/0269215520966702
|View full text |Cite
|
Sign up to set email alerts
|

Clinical effectiveness of peroneal nerve functional electrical stimulation in chronic stroke patients with hemiplegia (PLEASURE): A multicentre, prospective, randomised controlled trial

Abstract: Objective: To compare the effectiveness of gait training using a peroneal nerve stimulation device with the effectiveness of gait training without the device in improving gait ability and ankle-specific body functions. Design: Multicentre, prospective, randomised, open-label trial. Setting: Twenty-three hospitals. Subjects: In total, 119 stroke patients with foot drop were randomly assigned to the experimental (with the device) or control (without the device) group. Intervention: Subjects underwent 480-minute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
2
4
0
Order By: Relevance
“…The increase when FES is used is greater than with the use of conventional therapy, although some studies have reported no difference. 12,14,16,[21][22][23][24] In the comparisons before and after treatment, a significant improvement in walking speed was observed as in the current study. In other FES efficacy studies, it has been reported that the effect on walking speed was significant and this effect continued for up to 1 year on average.…”
Section: Parameterssupporting
confidence: 59%
See 1 more Smart Citation
“…The increase when FES is used is greater than with the use of conventional therapy, although some studies have reported no difference. 12,14,16,[21][22][23][24] In the comparisons before and after treatment, a significant improvement in walking speed was observed as in the current study. In other FES efficacy studies, it has been reported that the effect on walking speed was significant and this effect continued for up to 1 year on average.…”
Section: Parameterssupporting
confidence: 59%
“…This increase in walking speed can be considered to be related to regular walking activity and exercises. [17][18][19][20][21][22][23][24] In the current study, VGA showed significant improvements in ankle rotations and initial contact of the foot between the baseline and 4-week measurements. In parallel with this, a significant synchronisation with the normal side of the stance was observed.…”
Section: Parametersmentioning
confidence: 83%
“…Skin surface electrodes were placed at the proximal lateral condyles of the tibia to stimulate the peroneal nerve during the gait cycle. The frequency (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33), pulse width (100-300 µs) and intensity of the generated electrical pulse were customized to produce the desired dorsi exion during gait. The timing of tPNS activation and duration of stimulation were controlled by a tilt sensor and accelerometer according to the position and angle of the calf and speed of oscillation during the gait cycle.…”
Section: Foot Drop Stimulatormentioning
confidence: 99%
“…This clinically accepted rehabilitation intervention has been demonstrated to be more e cient than AFO, especially in terms of improving walking speed [22,23]. However, a multicenter prospective randomized study found that the use of peroneal nerve FES was equivalent to device-free gait training in terms of the clinical outcomes of improvements in walking speed, the Fugl-Meyer Assessment of Lower Extremity (FMA-LE) score, ankle muscle strength and dorsi exion performance [24].…”
mentioning
confidence: 99%
“…This clinically accepted rehabilitation intervention has been demonstrated to be more efficient than AFO, especially in terms of improving walking speed [ 22 , 23 ]. However, a multicenter prospective randomized study found that the use of peroneal nerve FES was equivalent to device-free gait training in terms of the clinical outcomes of improvements in walking speed, the Fugl–Meyer Assessment of Lower Extremity (FMA-LE) score, ankle muscle strength and dorsiflexion performance [ 24 ].…”
Section: Introductionmentioning
confidence: 99%